Comprehensive gene expression analysis of the NAC gene family under normal growth conditions, hormone treatment, and drought stress conditions in rice using near-isogenic lines (NILs) generated from crossing Aday Selection (drought tolerant) and IR64 - Nuruzzaman, M.; Sharoni, A.M.; Satoh, K.; Moumeni, A.; Venuprasad, R.; Serraj, R.; Kumar, A.; Leung, H.; Attia, K.; Kikuchi, S. (Springer, 2012)
The NAC (NAM, ATAF1/2 and CUC2) genes are plant-specific transcriptional factors known to play diverse roles in various plant developmental processes. We describe the rice (Oryza sativa) OsNAC genes expression profiles (GEPs) under normal and water-deficit treatments (WDTs). The GEPs of the OsNAC genes were analyzed in 25 tissues covering the entire life cycle of Minghui 63. High expression levels of 17 genes were demonstrated in certain tissues under normal conditions suggesting that these genes may play important roles in specific organs. We determined that 16 genes were differentially expressed under at least 1 phytohormone (NAA, GA3, KT, SA, ABA, and JA) treatment. To investigate the GEPs in the root, leaf, and panicle of three rice genotypes [e.g., 2 near-isogenic lines (NILs) and IR64], we used two NILs from a common genetic combination backcross developed by Aday Selection and IR64. WDTs were applied using the fraction of transpirable soil water at severe, mild, and control conditions. Transcriptomic analysis using a 44K oligoarray from Agilent was performed on all the tissue samples. We identified common and specific genes in all tissues from the two NILs under both WDTs, and the majority of the OsNAC genes that were activated were in the drought-tolerant IR77298-14-1-2-B-10 line compared with the drought-susceptible IR77298-14-1-2-B-13 or IR64. In IR77298-14-1-2-B-10, seventeen genes were very specific in their expression levels. Approximately 70 % of the genes from subgroups SNAC and NAM/CUC3 were activated in the leaf, but 37 % genes from subgroup SND were inactivated in the root compared with the control under severe stress conditions. These results provide a useful reference for the cloning of candidate genes from the specific subgroup for further functional analysis